Perubahan Paradigma Keagamaan (Studi Kasus Perubahan Paradigma Baru LDII di Kabupaten Nganjuk) - Hakim, Bashori A. (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2009)
Every single religion has its own doctrine for their worshippers. In the fact, those doctrines are interpreted according their own point of view so that sometimes happens certain group has dffirent interpretation to the other one. In Islam, an interpretation will be supported if it deliver the worshippers to happiness in life and deoth. This kind of interpretation has ever been developed by Darul Hadis or Islam Jamaah then become LEMKARI and finally well known with Lembaga Dakwah Islam Indonesia (LDII). This thought was considered to lose from Islamic instruction.